Additions to the knowledge of the Mutillidae (Hymenoptera) of Pakistan - Lelej, Arkady S.; Ullah, Mishkat; Mahmood, Khalid (Zootaxa, 2007)
Four species in four genera are newly recorded from Pakistan. Three of these species are new and are described: Smicromyrmilla margalla Lelej and Ullah, sp. nov. (Pakistan), Andreimyrme pakistanensis Lelej and Ullah, sp. nov. (Pakistan), and Ephutomma himalayana Lelej and Ullah, sp. nov. (Pakistan, Nepal). A new combination is proposed for Storozhenkotilla semiviolacea (André). Four genera are recorded for the first time from Pakistan: Smicromyrmilla Suárez, Storozhenkotilla Lelej, Andreimyrme Lelej, and Ephutomma Ashmead. The latter is recorded for the first time from Nepal. Storozhenkotilla semiviolacea (André) is recorded for the first time from Pakistan.